The development of macros program-based cognitive evaluation model via e-learning course mathematics in senior high school based on curriculum 2013 - Djoko Purnomo; Harjito Harjito; Rina Dwi Setyawati; Muhammad Prayito (Universitas Sebelas Maret, 2017)
The specific purpose of this research is: The implementation of the application of the learning tool with a form cognitive learning evaluation model based macros program via E-learning at High School grade X at july-december based on 2013 curriculum. The method used in this research followed the procedures is research and development by Borg and Gall [2]. In second year, population analysis has conducted at several universities in Semarang. The results of the research and application development of macro program-based cognitive evaluation model is effective which can be seen from (1) the student learning result is over KKM, (2) The student independency affects learning result positively, (3) the student learning a result by using macros program-based cognitive evaluation model is better than students class control. Based on the results above, the development of macros program-based cognitive evaluation model that have been tested have met quality standards according to Akker (1999). Large-scale testing includes operational phase of field testing and final product revision, i.e trials in the wider class that includes students in mathematics education major in several universities, they are the Universitas PGRI Semarang, Universitas Islam Sultan Agung and the Universitas Islam NegeriWalisongo Semarang. The positive responses is given by students at the Universitas PGRI Semarang, Universitas Islam Sultan Agung and the Universitas Islam NegeriWalisongo Semarang.